Alcohol consumption and binge drinking in adolescents: comparison of different migration backgrounds and rural vs. urban residence - a representative study - Bleich Stefan; Karagülle Deniz; Pfeiffer Christian; Baier Dirk; Gräßel Elmar; Donath Carolin; Hillemacher Thomas (BMC, 2011)
Abstract Background Binge drinking is a constant problem behavior in adolescents across Europe. Epidemiological investigations have been reported. However, epidemiological data on alcohol consumption of adolescents with different migration backgrounds are rare. Furthermore representative data on rural-urban comparison concerning alcohol consumption and binge drinking are lacking. The aims of the study are the investigation of alcohol consumption patterns with respect to a) urban-rural differences and b) differences according to migration background. Methods In the years 2007/2008, a representative written survey of N = 44,610 students in the 9th. grade of different school types in Germany was carried out (net sample). The return rate of questionnaires was 88% regarding all students whose teachers respectively school directors had agreed to participate in the study. Weighting factors were specified and used to make up for regional and school-type specific differences in return rates. 27.4% of the adolescents surveyed have a migration background, whereby the Turkish culture is the largest group followed by adolescents who emigrated from former Soviet Union states. The sample includes seven large cities (over 500,000 inhabitants) (12.2%), independent smaller cities ("urban districts") (19.0%) and rural areas ("rural districts") (68.8%). Results Life-time prevalence for alcohol consumption differs significantly between rural (93.7%) and urban areas (86.6% large cities; 89.1% smaller cities) with a higher prevalence in rural areas. The same accounts for 12-month prevalence for alcohol consumption. 57.3% of the rural, re-spectively 45.9% of the urban adolescents engaged in binge drinking in the 4 weeks prior to the survey. Students with migration background of the former Soviet Union showed mainly drinking behavior similar to that of German adolescents. Adolescents with Turkish roots had engaged in binge drinking in the last four weeks less frequently than adolescents of German descent (23.6% vs. 57.4%). However, in those adolescents who consumed alcohol in the last 4 weeks, binge drinking is very prominent across the cultural backgrounds. Conclusions Binge drinking is a common problem behavior in German adolescents. Obviously adolescents with rural residence have fewer alternatives for engaging in interesting leisure activities than adolescents living in cities. This might be one reason for the more problematic consumption patterns there. Common expectations concerning drinking behavior of adolescents of certain cultural backgrounds ('migrants with Russian background drink more'/'migrants from Arabic respectively Oriental-Islamic countries drink less') are only partly affirmed. Possibly, the degree of acculturation to the permissive German alcohol culture plays a role here.